Effectiveness of an Educational Program on Nurses' Knowledge and Practices about Prevent Complication for Patients Undergoing Thyroidectomy at Al-Hussein Teaching Hospital in Al-Nasiriyah City - Ali T. Hameed (Journal of Global Pharma Technology, 2018)
Thyroid surgery as any surgical procedure involves risks, which can cause life-threatening complications during the post-operative stage which includes (postoperative hemorrhage, respiratory obstruction, Infection, hypothyroidism, hypoparathyroidism, thyroid storm, and laryngeal nerve damage). So, educational programs concerning to prevent this complications is necessary to nurses to have practical skills and scientific knowledge to identify and detect early signs and symptoms of potential complications and take appropriate action, so early detection and fast response are vital to limiting damage and maintaining patient safety. For the purpose of evaluating effectiveness of an educational program on nurses' knowledge and practices about prevent complication for patients undergoing thyroidectomy in ICU and surgical wards at Al-Hussein teaching hospital in Al-Nasiriyah city; the researcher has constructed a questionnaire format in order to reach the objectives of the study. The questionnaire is consisting of (3) parts which are: Part I: demographic characteristics of the nurses such as (age, gender, and years of experience, educational level, and training courses). Part II: knowledge of nurses about prevent complication for patients undergoing thyroidectomy, it consists of (40) multiple choice questions in three Axes. Part III: The practices checklist for nurses (Observation checklist), is composed of (54) items divided into three part. Reliability of instrument was determined through the use intra examiner (test & retest), and inter examiners which is assessed by calculating alpha Cronbach, and the instrument validity was determined through a panel of (15) experts. The analysis of data was performed through the application of descriptive statistic (frequency, percentage, Mean of score (MS), Differences between pre-post Grand Mean of Score, Standard Deviation (SD), and (RS %) Relative Sufficiency) and Inferential statistical (Chi-Square test, Contingency Coefficients (C.C.) test, t-test, and (ANOVA) Analysis of Covariance). The results of the study showed that the effectiveness of an educational program on nurses' knowledge and practices about prevent complication for patients undergoing thyroidectomy in ICU and surgical wards are a positive. It also shows that there are highly significant differences in the study group between pre and post-tests in overall main domains related to nurses' knowledge and practice. The study concluded that the nurses working at ICU and surgical wards they really felt the gap in their knowledge and practices about prevent complication for patients undergoing thyroidectomy and they were aware of their lack of knowledge and their practices. So, this leads to conclusion that certainly in-service education should be provided for nursing staff to equip them to meet the new demands of nursing care based on latest technological advancement and knowledge explosion in the nursing. The study recommended that providing an educational programs should be ongoing for nurses to enhance their knowledge and skills about prevent complication for patients undergoing thyroidectomy. Also, Modern instructive facilities for nursing team at surgical wards should be provided to enhance nurse's knowledge and practices.Keywords: Effectiveness, Education Program, Nurses ꞌKnowledge &Practices, Prevent Complication, Thyroidectomy.